2003
DOI: 10.1109/tasc.2003.812063
|View full text |Cite
|
Sign up to set email alerts
|

Bi-2223 tapes - specific performance for different applications

Abstract: In the past (Bi Pb) 2 Sr 2 Ca 2 Cu 3 O Ag/Ag-alloysheathed High-Temperature Superconductor (HTS) tapes (Bi-2223 tapes) have been proven being suitable for building quite different system components for a variety of applications.Nevertheless it revealed that applications like Power Transmission Lines, Transformers, Motors/ Generators, SMES, very high field magnets and MRI put very special requirements on the tapes which differ from application to application.The most important point is that the tapes will provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Resistivity, susceptibility and magnetization experimental measurements in the Bi2223 compound (n = 3) show a transition to the superconducting state at ∼ 110 K [1,2]. In despite of the fact that this compound has a very high viability for its use in industrial and technological applications [3,4,5], we found surprisingly few theoretical reports.…”
Section: Introductionmentioning
confidence: 84%
“…Resistivity, susceptibility and magnetization experimental measurements in the Bi2223 compound (n = 3) show a transition to the superconducting state at ∼ 110 K [1,2]. In despite of the fact that this compound has a very high viability for its use in industrial and technological applications [3,4,5], we found surprisingly few theoretical reports.…”
Section: Introductionmentioning
confidence: 84%
“…The model can be used to choose an optimal preparation path for each individual application. Some results have already been presented [4]. For further analysis seven samples (denoted as A-G) were selected from the SEP work.…”
Section: Elementary Conductorsmentioning
confidence: 99%
“…In order to verify the reproducibility of the AC loss data, a number of tape samples were measured both at the University of Twente and at Siemens. The samples A-G were produced by EAS in the course of their loss optimization study [4]. Magnetization losses of these samples were measured as a function of an external field B(t) = B AC sin 2π f t both in parallel and perpendicular to the broad tape surface.…”
Section: Ac Loss Measurementsmentioning
confidence: 99%
“…In this work we present a detailed study of the electronic band structure, the density of states and the Fermi surface for Bi-2223. To our knowledge a theoretical study of this compound has not been yet reported in the literature in spite of the fact that the Bi-2223 compound is one of the most suitable HTSC materials for applications [11][12][13]. Neutron and X-ray diffraction experiments suggest that Bi-2223 presents several orthogonal structures with spacial groups Amaa, A2aa and F mmm [14][15][16] and a tetragonal structure with spatial group I4/mmm [17,18].…”
Section: Introductionmentioning
confidence: 99%